Auditor Economic Dependence and Accounting Conservatism: Evidence from a Low Litigation Risk Setting. (1st August 2012) - Liao, Yihsing; Chi, Wuchun; Chen, Yunshan
<x xml:space="preserve">Abstract</x> This study finds a negative relationship between an auditor's high degree of economic dependence on a client and the degree of accounting conservatism of the audited client in an environment with a low risk of litigation. We measure the economic dependence of auditors on their clients primarily through fees for non‐audit services. Our evidence suggests, however, that the negative effect on conservatism can be mitigated in firms that have higher board independence. The evidence from this study is highly relevant to the circumstances of East Asian economies, as well as to those of emerging countries in general.